(untitled) (World Bulletin of Education and Learning, 2025)
In this article, the second half of the 20th century was plagued by such problems that now, whether or not to escape from their torment has become the most urgent issue of our time. If at the end of the first half of the 20th century, humanity was faced with one universal problem - the prevention of nuclear annihilation, the situation changed after World War II. As a result, various types of predictions about the future of humanity emerged, and these problems are analyzed in the article.